Estimating Future Migration Flows Under Social and Environmental Scenarios Taking Into Account Interactions: Insights From a Survey Among Migration Scholars - Boissonneault, Michaël; Wieke de Jong, Petra (Frontiers in Human Dynamics, 2022)
Scenario planning has been gaining popularity during the last decade as a tool for exploring how international migration flows might change under unknown future circumstances. Using this technique, scholars have developed narratives that describe how flows might change depending on different developments in two of their most impactful and uncertain drivers. Current applications of scenario planning to migration however suffer from limitations that reduce the insights that can be derived from them. In this article, we first highlight these limitations by reviewing existing applications of scenario planning to migration. Then, we propose a new approach that consists in specifying different pathways of change in a set of six predefined drivers, to then ask migration scholars how each of these pathways might impact both migration flows and the other five drivers. We apply our approach to the case of migration pressure and demand from less developed countries to Europe until the year 2050. Results from our survey underscore the importance of a wide array of drivers for the future of migration that have so far not been considered in previous applications of scenario planning. They further suggest that drivers do not change independently from each other, but that specific changes in some drivers are likely to go hand in hand with changes in other drivers. Lastly, we find that changes in similar drivers could have different effects in sending and receiving countries. We finish by discussing how enhanced, quantified scenarios of migration between less developed countries and Europe can be formulated based on our results.